Ultrasonic Assisted Synthesis of Nano-Sized NaY Zeolite Composite from Metakaolin by Hydrothermal Method - XUE JING, W. (Asian Journal of Chemistry, 2010)
Nano-sized NaY zeolite has been synthesized from metakaolin by hydrothermal method with ultrasonic assisted during aging time. Its structure was characterized by XRD, SEM, TEM, HREM and its physicochemical properties and catalytic characteristics were studied. The results showed that the size of the product was about 100 nm, relative crystallinity being 80.12 %, Si/Al ratio being 5.12; compared with conventional zeolite, nano-sized zeolite has larger surface area and mesopore volume, better thermal stability, higher cracking activity, higher gasoline selectivity, lower coke and gas selectivity.